Topology optimization of quasistatic contact problems - Myśliński, Andrzej (Zielona Góra: Uniwersytet Zielonogórski)
This paper deals with the formulation of a necessary optimality condition for a topology optimization problem for an elastic contact problem with Tresca friction. In the paper a quasistatic contact model is considered, rather than a stationary one used in the literature. The functional approximating the normal contact stress is chosen as the shape functional
Keywords: quasistatic contact problem; elasticity; Tresca friction; topology optimization